2014
DOI: 10.1007/s12031-014-0256-0
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Increase in Ecto-5′-Nucleotidase Activity Overlaps with Appearance of Two Immunologically Distinct Enzyme Isoforms in Rat Hippocampal Synaptic Plasma Membranes

Abstract: Ecto-5'-nucleotidase (e-5NT), a glycosylphosphatidylinositol-linked membrane protein, catalyzes a conversion of AMP to adenosine, which influences nearly every aspect of brain physiology, including embryonic and postnatal brain development. The present study aimed to investigate a pattern of expression, activity and kinetic properties of e-5NT in the hippocampal formation and synaptic plasma membrane (SPM) preparations in rats at postnatal days (PDs) 7, 15, 20, 30 and 90. By combining gene expression analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…Based on the carbohydrate content, CD73 may be classified as a high-mannose type, complex carbohydrates type and hybrid type, which contains both complex carbohydrates and sialic acid residues ( Meflah et al, 1984 ; van den Bosch et al, 1986 , 1988 ; Wada et al, 1986 ; Baron and Luzio, 1987 ). As it is quite clear that the differences in glycosylation may be responsible for the variations found in apparent molecular weight of CD73 isolated from different sources ( Turnay et al, 1989 ; Olmo et al, 1992 ; Zimmermann, 1992 ; Navarro et al, 1998 ; Grkovic et al, 2014 ; Lavrnja et al, 2015 ), it has been increasingly evident that the variations in glycan content may be responsible for the functional differences of CD73 found in different cell types and tissues. Since glycans are charged molecules, changes in the carbohydrate composition of CD73 or incorporation of negatively charged sialic acid molecules ( Meflah et al, 1984 ), may significantly affect membrane charge density and thus cell behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the carbohydrate content, CD73 may be classified as a high-mannose type, complex carbohydrates type and hybrid type, which contains both complex carbohydrates and sialic acid residues ( Meflah et al, 1984 ; van den Bosch et al, 1986 , 1988 ; Wada et al, 1986 ; Baron and Luzio, 1987 ). As it is quite clear that the differences in glycosylation may be responsible for the variations found in apparent molecular weight of CD73 isolated from different sources ( Turnay et al, 1989 ; Olmo et al, 1992 ; Zimmermann, 1992 ; Navarro et al, 1998 ; Grkovic et al, 2014 ; Lavrnja et al, 2015 ), it has been increasingly evident that the variations in glycan content may be responsible for the functional differences of CD73 found in different cell types and tissues. Since glycans are charged molecules, changes in the carbohydrate composition of CD73 or incorporation of negatively charged sialic acid molecules ( Meflah et al, 1984 ), may significantly affect membrane charge density and thus cell behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Since glycans are charged molecules, changes in the carbohydrate composition of CD73 or incorporation of negatively charged sialic acid molecules ( Meflah et al, 1984 ), may significantly affect membrane charge density and thus cell behavior. Indeed, some earlier and recent studies demonstrate that the post-translational modifications of CD73 and alterations in the carbohydrate content may be responsible for a short-term ( Vogel et al, 1991 ; Schoen and Kreutzberg, 1994 ; Lavrnja et al, 2015 ) and long term ( Grkovic et al, 2014 ) regulation of CD73 functions, including its role in cell adhesion and migration. All these data point out that the regulation of CD73 by cells is a very complex mechanism, and include transcriptional and post-translational modification, together with cell-specific and tissue-specific regulators that have yet to be established.…”
Section: Discussionmentioning
confidence: 99%
“…NTPDase 2, which is the dominant ectonucleotidase expressed by progenitors in the late embryonic and adult mouse brain, has been identified from E18 in neurogenic regions [259,260], whereas NTPDases 1, 3, 5 and 6 are detected in later stages of brain development (P7-21) [261]. Concerning ecto-5´-ectonucleotidase, its expression increases during postnatal stages (it has been identified in migrating neuroblasts of the cerebellum and is related with synaptogenesis processes [192,[262][263][264][265]). Certain ectonucleotidases of the E-NNPs family are also expressed at early stages of neural development, such as E-NNP-2, for which the splice variant autotaxin was identified in the floor plate of the neural tube at E9.5 [266].…”
Section: Extracellular Purine Metabolism During Developmentmentioning
confidence: 99%
“…Moreover, it is found that expression and function of eN significantly increases in the hippocampal region from birth to adulthood, whereby eN-mRNA markedly increases from PD7 to PD20, reaching a plateau, while the enzyme activity continued to increase beyond this age. Namely, at PD7, the eN gene is weakly expressed concomitant with poor enzyme activity in most hippocampal fields, while in some subregions the activity was completely absent [114]. Further analysis also reveals that layers rich in synapses generally displays the highest levels of eN activity, while in neuronal cell bodies layers, the enzyme expression is weak or completely absent.…”
Section: Ectonucleotidases During Cns Develop-mentmentioning
confidence: 99%
“…To date, there is only scarce information concerning the role of ATP, other nucleotides as well as expression pattern of individual ectonucleotidases in the development of synaptic network activity, although it is shown by several studies that synaptic compartments comprise ectonucleotidases, i.e . NTPDase1–3, eN, [68, 87, 100, 114, 115, 126, 132-134]. It is also found that TNAP is selectively expressed in the synaptic cleft of sensory cortical areas in adult primates [69] and in humans [135] and its activity is regulated by sensory experience in the primate visual cortex [82].…”
Section: Implication Of Ectonucleotidases In Synapse Formation Maturmentioning
confidence: 99%